Chronobiology: The Circadian Clock under Extreme Photoperiods - Doležel, David (Current biology, 2019)
Circadian clocks are time-measuring devices found in a majority of organisms synchronizing their behavior and metabolism with the day-light cycle. What happens in extreme latitudes, where the environmental conditions can be harsh at any time of day?
Keywords: Circadian Rhythm; Darkness; cirkadiánní hodiny; Photoperiod; Circadian Clocks; fotoperioda; tma; cirkadiánní rytmus